Scalp reconstruction using the latissimus dorsi free flap: a 12-year experience - Strübing, Felix; Wenz, Fabian; Etminan, Nima; Bigdeli, Amir K.; Siegwart, Laura C.; Thomas, Benjamin; Vollbach, Felix; Vogelpohl, Julian; Kneser, Ulrich; Gazyakan, Emre (Journal of Clinical Medicine, 2023)
Background: Complex scalp defects are regularly reconstructed using microvascular tissue transfer. The latissimus dorsi free flap is one of the workhorse flaps used in scalp reconstruction. These cases necessitate, particularly in the elderly, a close cooperation between plastic surgeons and neurosurgeons. The purpose of this study was to evaluate the suitability of the latissimus dorsi free flap for complex scalp reconstructions and to analyze potential risk factors. Methods: A retrospective study identified 43 patients undergoing complex scalp reconstruction using a latissimus dorsi free flap at our department between 2010 and 2022. Results: The mean patient age was 61 ± 18 years. Defects were mostly caused by oncologic tumor resections (n = 23; 55%), exposure to a cranioplasty (n = 10; 23%) or infection (n = 4; 9%). The most frequent recipient vessels were the superficial temporal artery (n = 28; 65%), external carotid artery (n = 12; 28%) and the venae comitantes (n = 28; 65%), external jugular vein (n = 6; 14%). The reconstructive success rate was 97.7%. There was one total flap loss (2%). Partial flap loss occurred in five cases (12%). Follow-up was 8 ± 12 months. Major complications were seen in 13 cases, resulting in a revision rate of 26%. Multivariate logistic regression identified active tobacco use as the only risk factor for major complications (odds ratio 8.9; p = 0.04). Conclusion: Reconstruction of complex scalp defects using the latissimus dorsi free flap yielded high success rates. Among the potential risk factors, active tobacco use seems to affect the outcome of complex scalp reconstructions.
Gesehen am 09.06.2023